The Compatibility of Romania's Industrial Policy with That of the European Union - Petronela Nica (CES Working Papers, 2010)
Romania s position as one of the EU member states brought new challenges in terms of industrial policy, in order to respond to the necessity of bringing the competitiveness level of the Romanianeconomy close to the average level of the European states, by respecting the free trade principles of the European Union. Furthermore, in the near future Romania should be able to contribute to the achievement of the objective of transforming EU in the most competitive economy of the world. In this order, a market – oriented industrial policy is necessary, following the European industrial policy and the sustainable development concepts adopted by the European Commission, and based on the concept of competitiveness.The general purpose of a balanced economic growth, sustainable development and improvement of the economic competitiveness requires industrial policies created and implemented in tight connection withother relevant economic policies, such as the competition policies, those aiming for a functional business environment and those encouraging the SME development and attracting FDE, the policies in the educationand research and development fields, the structural and regional policies, the commercial policies, the sustainable development and environment protection policies and those regarding employment and social cohesion.
Keywords: 330; Industrial policy; competitveness; European Union; competition policy; structural policy; regional policy; sustainable development